Research on a hydrate saturation prediction method based on an analysis of factors that influence the prediction accuracy of sea area hydrate saturation - Bao, Xiangsheng; Luo, Tianyu; Li, Huadong; Li, Jiusheng; Chen, Guomin; Mi, Fang; Cai, Zhanhu; Chen, Huapeng (Frontiers in Earth Science, 2022)
It is predicted that China has about 80 billion tons of oil equivalent of natural gas hydrate resources in the sea. China has conducted at least six drilling and two trial exploitation in the South China Sea, and achieved good achievements.However, these achievements do not mean that the research area can achieve commercial exploitation. Only when the natural gas hydrate resources in the research area reach a certain scale, it has the value of commercial exploitation.To make clear the scale of gas hydrate in the research area, it is necessary to have a reliable quantitative prediction method. However, when the classical Wood method is applied to the prediction of suspended hydrate saturation in the Shenhu sea area of China, the prediction error is large, and the analysis shows that the unreliable measurement of reservoir parameters is the main reason for the large prediction error.In order to clarify the influence of reservoir parameters, firstly, by analyzing the sources of measurement parameters of reservoir parameters, this paper points out that inaccurate measurement of three reservoir parameters including matrix composition, porosity and density is the main cause of prediction error. Then according to the design of different reservoir parameters measurement scheme to carry out comparative analysis,this paper points out that unreliable porosity and density measurement may lead to large prediction errors, while unreliable matrix composition measurement has a relatively small impact on prediction accuracy. Further analysis show that, the absolute value of prediction error caused by synthetic reservoir parameter measurement uncertainty is sometimes larger than the sum of the absolute prediction error caused by the single parameter measurement uncertainty.Aiming at the problem of large prediction error caused by inaccurate measurement of reservoir parameters, this paper proposes a hydrate saturation prediction method based on non-hydrate correction, called Wood-Bao method. Simulation and actual data studies show that the prediction effect of this method is much better than that of Wood method.